2021
DOI: 10.2298/fil2110319b
|View full text |Cite
|
Sign up to set email alerts
|

Optimal inequalities for submanifolds in statistical manifolds of quasi constant curvature

Abstract: In this paper, we establish B.-Y. Chen?s optimal inequalities for statistical submanifolds involving Casorati curvature and the normalized scalar curavture in a statistical manifold of quasi constant curvature. The equality cases of these inequalities are also considered. Further, we provide some applications of our results. Moreover, as a new example we construct minimal statistical surface (statistical submanifold) of a statistical manifold of quasi constant curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In 2018, H. Aytimur and C. Özgür [198] studied statistical submanifolds of statistical manifolds of a quasi-constant curvature in which they obtained the Chen-Ricci inequality and generalized the Wingten inequality. In [199], P. Bansal, S. Uddin and M. H. Shahid derived a first Chen-type inequality for statistical submanifolds of a statistical manifold of a quasi-constant curvature. Also, G. He, J. Zhang and P. Zhao derived in [200] a first Chen-type inequality for a statistical submanifold of a statistical manifold M of a constant curvature, such that M admits a nonintegrable distribution on M with a constant rank.…”
Section: Inequality For Statistical Submanifolds Of Statistical Manif...mentioning
confidence: 99%
“…In 2018, H. Aytimur and C. Özgür [198] studied statistical submanifolds of statistical manifolds of a quasi-constant curvature in which they obtained the Chen-Ricci inequality and generalized the Wingten inequality. In [199], P. Bansal, S. Uddin and M. H. Shahid derived a first Chen-type inequality for statistical submanifolds of a statistical manifold of a quasi-constant curvature. Also, G. He, J. Zhang and P. Zhao derived in [200] a first Chen-type inequality for a statistical submanifold of a statistical manifold M of a constant curvature, such that M admits a nonintegrable distribution on M with a constant rank.…”
Section: Inequality For Statistical Submanifolds Of Statistical Manif...mentioning
confidence: 99%
“…In recent years, during literature reviews on statistical submanifolds, it has been observed that studies have focused on Chen inequalities ( [5], [6], [15], [53]),Wintgen inequalities ( [8], [25], [44]) and inequalities involving the normalized δ-Casorati curvatures ( [12], [16], [17], [26], [38], [54]).…”
Section: Introductionmentioning
confidence: 99%